ASSOCIATION BETWEEN THE USE OF LICIT SUBSTANCES IN UNIVERSITY STUDENTS: INTEGRATIVE LITERATURE REVIEW (CIPEEX, 2025)
The use of legal substances among university students has become a public health problem. These students are more prone/susceptible to developing illnesses, premature deaths and addiction. This study aims to analyze the relationship between the use of legal substances in university students. This is an integrative review of the literature, developed from bibliographic material obtained from databases such as: Scielo, Lilacs, PubMed, BVS. Data collection involved a thorough analysis of the literature to obtain a complete understanding of the topic. 28 articles are considered; After the exclusion criteria and reading of the titles and abstracts, 10 remained for the construction of the study. The results obtained through this research highlight that this study scenario reveals a worrying reality that affects the health and lives of university students. After reaching the end of this study, it becomes clear that, unfortunately, the increase in the use of these legal substances is a common problem among academics at different universities and has affected more and more students.
Keywords: yound people; university; susbtances; review